Analisis Data Mining dalam Prediksi Pertumbuhan Penduduk Kabupaten Serdang Bedagai Menggunakan Regresi Linear Berganda - Azizah Wulan Lestari; Lisa Salsabila Sinaga; Juwita Samroiyah Pulungan; Ulifia Cahaya Hasibuan; Ismail Husein (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Population growth is an important indicator in regional development planning because it influences the provision of public services, infrastructure development, and policy formulation. Accurate population estimation is therefore essential to support data-driven decision-making by local governments. This study aims to estimate the population growth rate of Serdang Bedagai Regency by applying data mining techniques using the Multiple Linear Regression method. The data used were obtained from the Central Statistics Agency (BPS) of Serdang Bedagai Regency for the period 2019–2023 and include the number of male and female residents. The research process involved several stages, including data collection, data preprocessing, model development, and statistical analysis. Based on the analysis, a regression model was obtained with the equation Y = 0 + 1.5558X1 + 0.4367X2, where Y represents the total population, X1 represents the number of male residents, and X2 represents the number of female residents. The results indicate an estimated population of 683,056 people in 2024, showing an increase compared to the previous year. These findings suggest that the Multiple Linear Regression method can provide reliable population estimates and serve as a useful reference for supporting evidence-based regional development planning and population management strategies in Serdang Bedagai Regency.